Le Zebu de Madagascar - Guillermo, M. (1949)
Describes the general characteristics and origin of zebu animal breed. Data on rearing zone, body measurements, milk production, meat quality and genetic characteristics included. Methods of maintenance and improvement of Madagascar Zebu recommended.